Anatomical properties of various palm fronds oil palm, coconut palm and date palm / Mohd Irwan Wahab - Wahab, Mohd Irwan (2001)
Anatomical properties of oil palm, coconut palm and date palm based on part of fronds section. The source of oil palm and coconut palm fronds were from Sungai Tekam Utara meanwhile date palm frond were from Kota Gelaggi, Pahang. Anatomical properties that had in these fronds were it has a same cell structure. There are metaxylem (vessel), metaphloem, extended protoxylem and fibre in the vascular bundle. It can be concluded, there are differences at number of vessel cell which in vascular bundle. So we can know the differences between oil palm, coconut palm and date palm.